Ehl-i Sünnet Açısından Bilgi ve Değeri Knowledge and its Value in Terms of the Ahl As-Sunnah - yücedağ, ismail (Journal of History Culture and Art Research, 2014)
Kelâm ilmînin amacı, dinî inançları kesin deliller kullanarak ispat etmektir. Bu nedenle kelâmcılar Kur’an’ı ve iki kısma ayırdıkları Sünnet’in ilk kısmında yer alan mütevâtir haberleri esas almışlardır. Kelâm ilminde üç bilgi edinme yolu olduğu kabul edilmiştir. Bunlar, beş duyu, akıl ve haber-i sâdık’tır. Bilgi edinme yollarından ilk ikisini oluşturan beş duyu ve akıl ile elde edilen bilgiler ile Sünnet’in ilk kısmında yer alan mütevâtir haberin değeri konusunda İslâm âlimleri arasında bir ihtilâf söz konusu değildir. Hicretin II. asrından itibaren, sünnetin ikinci kısmını oluşturan haber-i vahid’in değeri ve itikâdî konularda delil teşkil edip etmeyeceği konusunda âlimler tarihsel süreç içinde birbirinden farklı görüşler ortaya koymuşlardır. Böylelikle problem günümüze kadar devam etmiştir. Konu hakkında fikir yürüten âlimler, Kelâmcılar ve Selefiyye olmak üzere iki ana gruba ayrılmışlardır. Bu çalışmanın amacı, haber-i vâhid hakkındaki fikir ayrılıklarının nedenlerini, kelâmcılar tarafından bilgi edinme yollarından biri olarak kabul edilen haber-i sâdıkı dikkate alarak araştırmaktır. AbstractThe purpose of the Kalam science is to prove the religious beliefs by using definitive evidences. For this reason, the Kalam scholars are inclined to Koran and the mutawatir reports which are included in the first part of Ahl As-Sunnah divided into two parts. In the Kalam science, it has been accepted that there are three ways of attaining knowledge. These are the five senses, intelligence, and precise reports. It is not the case that Islamic scholars have a disagreement on not only knowledges obtained through the five senses and intelligence but the value of mutawatir reports included in the first part of Ahl As-Sunnah. As of the second century of Hegira, the scholars have put forward different opinions about whether the value of imprecise reports will constitute an evidence in matters of faith in the historical process or not. Thus, the problem has continued to the present day. The scholars who speculate about the issue have been divided into two main groups as Kalam scholars and Salafism. The purpose of this study is to research the reasons for the disagreements on imprecise reports by taking precise reports into account, which has been accepted by Kalam scholars as one of the ways of attaining knowledge.